Near‐infrared dye‐labeled antibody COC183B2 enables detection of tiny metastatic ovarian cancer and optimizes fluorescence‐guided surgery. Issue 6 (23rd July 2020) - Chen, Junchen; Guo, Yanxiu; Li, Hui; Zhang, Chen; Chang, Xiaohong; Ma, Ruiqiong; Cheng, Hongyan; Ye, Xue; Cui, Heng; Li, Yi
Abstract: Objective: We aimed to evaluate the ability of the fluorescent monoclonal antibody probe COC183B2‐Cy7 (Cy7‐conjugated COC183B2 antibody) to detect tiny metastatic lesions of ovarian cancer and thus guide precise tumor resection. Methods: The expression of the tumor‐associated antigen OC183B2 in lymph nodes and SKOV3‐Luc cells was detected using immunohistochemistry and immunofluorescence. A subcutaneous mouse tumor model and an intraperitoneal ovarian cancer metastasis model were constructed using SKOV3‐Luc cells. Near‐infrared fluorescence (NIRF) imaging was performed to determine the imaging parameters and evaluate the ability of COC183B2‐Cy7 to detect tiny metastatic lesions. Results: OC183B2 was expressed in metastatic lymph nodes and SKOV3‐Luc cells. NIRF imaging of the subcutaneous mouse tumor model showed that the tumor background ratio was significantly higher in the COC183B2‐Cy7 group than in the control group at different time points postinjection. Biodistribution study showed that COC183B2‐Cy7 did not accumulate in other organs. COC183B2‐Cy7 can detect tiny metastatic lesions of ovarian cancer. The smallest intraperitoneal metastatic tumor detected by COC183B2‐Cy7 was approximately 1 mm. Conclusions: COC183B2‐Cy7 probe has relatively high specificity and sensitivity. Our study suggests that COC183B2‐Cy7 probe is a promising diagnostic tool for the complete and accurate resection of malignant lesions in fluorescence‐guided surgery.